Metodológicas activas y aprendizaje de matemática en octavo de educación general básica, unidad educativa intercultural bilingüe Totoras, septiembre-diciembre 2021 - Guaranga Tenegusñay, María Hilda (2022)
The present research work addresses the active methodologies and their relationship with the learning of mathematics in the eighth grade students of E.G.B. It is framed in an educational context, observed that currently, the quality of student learning depends directly on the strategies used by teachers, these are the ones that allow fostering the interest of students in the subject and thus achieve a good level of knowledge. student achievement; therefore, teachers must work on different strategies that allow their students to understand and arouse interest in the subject and not simply that the students pass it. The methodology used in this research was of non-experimental design, the type of research was descriptive since a quantitative analysis of the study variables was carried out, as well as a brief description of the main elements, the population with which they worked was 56 students who were surveyed using techniques and instruments for data collection relating to active methodologies and their relationship with learning mathematics. As a conclusion, it is determined that the active methodologies focused on the teaching of mathematics are: the Inverted Classroom and the PBL, however, the use of these methodologies is low since it is evident that the students only care about passing the subject and not in learn, because most of the time the teacher uses a traditional methodology, and active methodologies are rarely used for learning.